An elucidatory model of oxygen's partial pressure inside substomatal cavities - A. S. Kowalski; A. S. Kowalski (Biogeosciences)
A parsimonious model based on Dalton's law reveals substomatal cavities to be dilute in oxygen (O2), despite photosynthetic O2 production. Transpiration elevates the partial pressure of water vapour but counteractively depresses the partial pressures of dry air's components – proportionally including O2 – preserving cavity pressurization that is negligible as regards air composition. Suppression of O2 by humidification overwhelms photosynthetic enrichment, reducing the O2 molar fraction inside cool or warm leaves by hundreds or thousands of parts per million. This elucidates the mechanisms that realize O2 transport: diffusion cannot account for up-gradient conveyance of O2 from dilute cavities through stomata to the more aerobic atmosphere. Rather, leaf O2 emissions depend on non-diffusive transport via mass flow forced by cavity pressurization, which is not negligible in the context of dynamics. Non-diffusive O2 expulsion overcomes massive inward O2 diffusion to force net O2 emission. At very high leaf temperatures, mass flow also influences transport of water vapour and carbon dioxide, physically decoupling their exchanges and reducing water-use efficiency, independently of stomatal regulation.